Η δια-πραγμάτευση του μέγιστου με την ποιητική του ελάχιστου - Κωτόπουλος Tριαντάφυλλος (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
The literary text does not only constitute a socially morphed product that takes into consideration the historical and social circumstances which created it, but at the same time it is an aesthetic product, an art product, that is, of the particular artistic intervention of its creator. In the following text, we attempt to approach dialectically the book series by Veggelis Iliopoulos, containing Trigonopsaroulis, a unique character, in a way that takes into account the extratextual historical and social coordinates of the literary text, to the extent that these are expressed as connotations in a semantic level through the productive process of writing.